“MUSLIM PROGRESIF” OMID SAFI DAN ISU-ISU ISLAM KONTEMPORER - Ali Murfi; Rahmad Nursyahidin (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2015)
The research reveals about the thought of Omid Safi about Progressive Muslims from naming, agenda, attendance reasons, to focus them on the realm of Islamic thought and relate it to trends in contemporary Islam. Progressive Muslim intended as an umbrella concept for people who want an open and safe space for running a rigorous and honest engagement with tradition, and hopefully will lead to further action. There are three major agenda (mission) of Progressive Muslims, the first social justice; both gender equality; The third received a plurality. The method adopted by Omid Safi in constructing the concept of Progressive Muslims are methods Multiple Critique. Progressive Muslims in an attempt to compare with trends in contemporary Islam is indeed a lot of help affirm the distinction in each trend. However, when we conducted an analysis of eight classification proposed by Abdullah Saeed on trends in contemporary Islam, seemingly progressive Muslims more fit in the category of groups ijtihadi Progressive, which modern thinkers on religion which seeks to reinterpret religious teachings in order to answer kebutuham modern society and Saeed himself quoting Omid Safi when defining trends of this last one.